An Optimizating the Software Metrics for UML Structural and Behaviourl Diagrams using Metrics Tool: Optimizating the Software Metrics for UML Structural and Behaviourl Diagrams using Metrics Tool - Singh, Daljeet (INFOCOMP Journal of Computer Science, 2019)
In this paper, we have proposed an efficient way to calculate the software metrics of structural and behavioural diagrams of unified modelling language (UML) with the help SD Metrics as a tool. This method is applied to measure the internal quality of attributes and functions of structural and behavioural diagrams of unified modelling language (UML). The SD metrics tool collect the information after parsing the XMI format generated by UML compiler of structural and behavioural UML diagrams. The object-oriented design made by structural and behavioural diagrams holds the important part of designing in the development process of the software. Early the measurement of metrics will lead to good quality of the software from coding, but now using the design metrics we calculate the cohesion, coupling and other metrics with easy and effectively with the fewer efforts which improve the quality of software to be developed at the design phase